Hubungan Kelentukan Pergelangan Tangan Terhadap Kemampuan Servis Forehand Backspin Tenis Meja - arifianto, *irfan; _, Suhermon (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
This study aims to determine the relationship between wrist flexibility and forehand back spin service skills. This research is a type of correlational research. The population in this study can be said to be 20 athletes. Sampling was carried out using purposive sampling technique based on the objectives set by the researcher who assessed 15 male athletes. The research instrument through wrist flexibility tests and service skills tests were carried out by service skills tests. Data analysis techniques used current product data analysis techniques (simple display and multiple views) with a significant level of Î± = 0.05. The results showed a significant contribution between wrist flexibility and forehand back spin skills in junior athletes of PTMSI Padang Pariaman with a coefficient value of rcount 0.83> rtabel 0.514 and distribution coefficient of tcount 5.77 > ttable 1.75.